Sportspeople Tracking in the Mountains: a Methodological Proposal for the Spatial Analysis of GPS Data Produced by Trail Runners - Camille Savre; Marie Eveillard-Buchoux (Revue de Géographie Alpine)
The aim of this article is to determine how GPS data produced by sportspeople can be useful in understanding the spatial uses of mountains. It presents an exploratory methodology carried out on routes recorded by trail runners and uploaded to the sports social network Strava™. Our methodology proposes to categorise the routes with elevation and distance criteria. The spatial translation of this categorisation will then be observed to understand the behaviour of sportspeople in their practice area. In a context where sporting activities offer new forms of human presence in mountain environments, this article provides a better understanding of sports practices in the mountains. This methodology paves the way for using geodata to analyse individual behaviour on a qualitative basis. It may complement other qualitative surveys and quantitative approaches, thus meeting the complex challenges of managing mountain environments.